Time-varying stochastic frontier model approach for measuring female parliamentarian efficiency of selected countries in Asia - Najeebullah Khan; Md. Azizul Baten; Mohammad Muqtada Ali Khan; Shafiqur Rahman (American-Eurasian Network for Scientific Information (AENSI), 2014)
The study considers stochastic frontier model to investigate the technical efficiency of randomly selected eight Asian countries namely Pakistan, China, India, Bangladesh, Indonesia, Thailand, Philippine and Malaysia applied to unbalanced panel data sets for the period 2002-2010.A half-normal distribution assumption with a simple specification of the time-varying inefficiencies was incorporated to the model. A Cobb-Douglas stochastic frontier production function with time-varying technical inefficiency effects was estimated.Year wise mean technical efficiency of the parliament of eight Asian countries during the reference period decreased from 46.8-42.8%. Among the selected Asian countries, China and Pakistan were experienced highest (87.58%) and lowest (33.40%) parliament mean efficiencies, respectively.In case of time-invariant inefficiency effect model, the estimated overall average technical efficiency was found 54.96% for the parliament of selected Asian countries and it is of potential output for the half-normal distribution.